Battle of the Bands: The Psalter vs. Demonic Noise - Abbott, Philip (2024)
When scholars discuss the use of the Psalms in early Christianity, they typically underscore how the Psalter functioned as an instrument to harmonize the self with the divine. In other words, the Psalms transformed Christian readers, allowing them to internalize the Gospel and exorcize their inner demons. This article argues, however, that there is a more externalized aspect of apotropaism to the Psalter in the writings of Athanasius. According to the bishop of Alexandria, the Psalter had real prophylactic power against embodied evil forces. Conceptualizing the Book of Psalms as an aural incarnation of Jesus that anticipated his physical incarnation, Athanasius believed that the Psalter contained Christ’s presence and could be employed to drive demons out of their strongholds and Christianize the landscape. In his Life of Antony, Athanasius’ Antony uses the Psalter in this manner as he advances into demonic territory and threatens demonic hegemony. In response, demons launch sonic attacks of their own on the great ascetic, producing a terrible cacophony. More than mere distraction, this demonic noise signifies resistance to the shifting power dynamics in the unseen realm. Thus, Life of Antony recounts a holy battle of the bands, where Christ via the Psalter competes with the devil and his motley crew of noisy demons.